OIL PRICE SHOCKS AND THEIR IMPACT ON ECONOMIC ACTIVITY IN IRAQ (American Journal of Business Management, Economics and Banking, 2024)
This research aims to shed light on the most important and prominent economic problem that Iraq suffers from, which is its dependence on crude oil exports to finance its current and investment expenses and maintain the value of the national currency, as Iraq’s non-oil exports are very limited. Therefore, the research problem focuses on the fact that the Iraqi state depends Almost entirely on oil revenues to finance public expenditures, and since oil is a commodity that can be depleted shortly and oil prices are constantly fluctuating, this means that Iraq’s economy is not sustainable and that it will be exposed to ongoing crises and perhaps to a complete collapse of economic conditions. To obtain clear results that cannot be doubted, the study included annual data from the year 2004 to the year 2022.The research included a group of dependent variables, including economic, financial, and monetary, that would give a clear vision of the problem regarding oil prices, which represents the independent variable, and it was adopted. On the descriptive analysis of the data table to give a general and clear view of the impact of oil prices on the dependent variables, the research reached a set of conclusions, the most important of which is first: The significant decline in oil prices, i.e. less than $50, negatively affects all economic indicators, the most important of which are the Central Bank of Iraq’s oil reserves. Foreign currencies.Secondly: When there is a significant decline in state revenues due to the decline in oil prices, the greatest damage is to investment spending, not current spending. This means that the segment most affected are non-employees, and they are multiple categories.The most important recommendations are: The developed countries are working hard to gradually abandon fossil fuels in the future or significantly reduce dependence on them. They have set time programs for this goal. On the other hand, we must develop strategic plans to gradually reduce dependence on oil so that we notice a difference year after year.